Gross Tumor Volume Predicts Survival and Pathological Complete Response of Locally Advanced Esophageal Cancer After Neoadjuvant Chemoradiotherapy - Wang, Rong; Zhou, Xiaomei; Liu, Tongxin; Lin, Shuimiao; Wang, Yanxia; Deng, Xiaogang; Wang, Wei (Frontiers in Oncology, 2022)
Background Neoadjuvant chemoradiotherapy (neo-CRT) plus surgery has greatly improved the prognosis of locally advanced esophageal cancer (EC) patients. But which factors may influence the pathological tumor response and long-term survival remains unclear. The purpose of this study was to identify the prognostic biomarkers of locally advanced EC patients receiving neo-CRT. Methods We reviewed the data of 72 patients with cT2-4N0-3M0 EC who underwent neo-CRT at our hospital. The patients received intensity-modulated radiation therapy with a total radiation dose of 41.4–60.0 Gy. Most patients received platinum + paclitaxel-based combination regimens every three weeks for 2–4 cycles. The recorded data included age, sex, smoking history, alcohol use, histology, tumor location, clinical TNM stage, tumor length, gross tumor volume (GTV), GTV of primary tumor (GTVp), GTV of lymph nodes (GTVn), radiation dose, and number of chemotherapy cycles. Overall survival (OS), progression-free survival (PFS), and pathological complete response (pCR) were analyzed. Results The 3-year OS and PFS rates of these patients who underwent neo-CRT were 51.14% and 43.28%, respectively. In the univariate analyses, smoking history, clinical stage, GTV, GTVp, and GTVn were significantly associated with OS, whereas alcohol use, GTV, GTVp, and GTVn were significantly associated with PFS. Furthermore, in the multivariate analysis, GTV was an independent prognostic predictor of OS (hazard ratio (HR): 14.14, 95% confidence interval (CI): 3.747–53.33, P < 0.0001) and PFS (HR: 6.090, 95% CI: 2.398–15.47, P < 0.0001). In addition, GTV < 60.50 cm3 compared to > 60.50 cm3 was significantly associated with higher pCR rate (59.3% and 27.8%, respectively, P = 0.038). High dose (> 50 Gy) and increased number of chemotherapy cycles (≥ 3) didn’t improve the OS or PFS in patients with GTV > 60.50 cm3. Conclusion GTV was an independent prognostic factor of long-term survival in EC patients, which may be because GTV is associated with histological response to neo-CRT. Additionally, patients with GTV > 60.50 cm3 didn’t benefit from increased radiation dose or increased number of chemotherapy cycles.